[Memorandums from campus administration to ASI, 1972] - Everett Chandler::::::author:::; Robert E. Kennedy::::::author::: (1972)
Memorandum from Dean of Students Everett Chandler to ASI Secretary Debbie Meadows. Chandler is writing to explain why the administration decided to deny recognition to the proposed Gay Student Union. Letter from Robert E. Kennedy to Meadows about "Dorm Congress". Administrative Response to Student Affairs Council May 26, 1972, Request Regarding Residence Halls.